PEMANFAATAN FLOWCHART DALAM PENINGKATAN KINERJA ORGANISASI PENDIDIKAN - Mandela, Rahmat Yoza; Sohiron, Sohiron (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of flowcharts as a strategic instrument in improving the performance of educational organizations, with a scope covering administrative, academic, and curriculum development aspects. Through a qualitative literature study approach to academic sources (journals, books, quality guides) published between 2010 and 2025, it was found that the systematic application of flowcharts can simplify procedures, reduce redundancy, minimize procedural errors, and accelerate responses to change. Key findings indicate that educational organizations that integrate flowcharts into their operational governance tend to be more transparent, accountable, and adaptive to the dynamics of the modern educational environment. In conclusion, flowcharts are not merely technical tools, but rather essential managerial strategies in the transformation of educational organizations towards process-based governance. The implication is that educational institutions are advised to adopt flowcharts as an integral part of their quality management systems and integrate them into digital platforms for real-time updates.